Pengaruh Gaya Kepemimpinan Dan Efektivitas Sistem Pengendalian Internal Terhadap Fraud (Studi Kasus Pengadaan Barang Di PT Kaltim Industrial Estate) - Tyagita Dianingtyas Sudibyo (Jurnal Perilaku dan Strategi Bisnis, 2020)
This porpuse of this research is to find out the leadership style used by leader to fraud in the procurement of goods at PT Kaltim Industrial Estate. This research is quantitative research that used primary data be obtained from questionnaire. The question are closed-ended with likert scale method.          The research population are all of the employee PT Kaltim Indusrial Estate. The research sample are 36 respondent in procurement of goods at PT Kaltim Industrial Estate. The teqnique of this research is using SmartPLS program to analyzing the data.          The result of research indicates (1) the democracy leadership style is used in procurement of goods at PT Kaltim Industrila Estate, (2) the leadership style negatively effect to fraud in procurement of goods at PT Kaltim Industrial Estate, (3) effectiveness of internal control system negatively effect to fraud in procurement of goods at PT Kaltim Industrial Estate.